Relationships of demographic factors to the dental health knowledge and to the oral hygiene practices of the residents of Golden Acres - David, Myriam R.; Murjani, Bhabita (Adviser).
Dental health and oral hygiene are not of high priority, particularly among the older adults in the country. Most elderly persons have certain beliefs that may be influenced by certain factors. This study is focused on the demographic factors such as gender, educational attainment, dentition status and place of origin. This study aimed to measure dental health knowledge of the sample population from the Golden Acres Home for the Aged, and to determine how they practice oral hygiene . This study also aimed to determine significant relationships between the following: Demographic Factors and Dental Health Knowledge (DHK) and Demographic Factors (DF) and Oral Hygiene Practices. A one on one interview with the formulated questionnaire was conducted among the 94 residents of Golden Acres. Convenience sampling was performed. Findings revealed that: a) Dental Health Knowledge of the residents were mostly of good and excellent levels. No correlation with Demographic Factors was found and b) Oral Hygiene Practices of the residents were satisfactory and that attention be focused on regular dental visits and check-ups. No correlation with Demographic Factors was found.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.